An assessment tool for puck control in ice hockey - Chmelír, L.; Peric, T.; Štochl, J. (Sport Sciences for Health, 2025)
Purpose In the field of ice hockey, scientific-based methods focus primarily on assessing non-specific motor skills. To assess specific skills, "expert" opinion is used. In this paper, we outline the use of item response theory and Guttman scale techniques to develop a puck control assessment tool tailored for ice hockey players aged from 6 to 15 years.